Tool Use by Four Species of Indo-Pacific Sea Urchins - Glyn A. Barrett; Dominic Revell; Lucy Harding; Ian Mills; Axelle Jorcin; Klaus M. Stiefel (Journal of Marine Science and Engineering, 2019)
We compared the covering behavior of four sea urchin species, Tripneustes gratilla, Pseudoboletia maculata, Toxopneustes pileolus, and Salmacis sphaeroides found in the waters of Malapascua Island, Cebu Province and Bolinao, Panagsinan Province, Philippines. Specifically, we measured the amount and type of covering material on each sea urchin, and in several cases, the recovery of debris material after stripping the animal of its cover. We found that Tripneustes gratilla and Salmacis sphaeroides have a higher affinity for plant material, especially seagrass, compared to Pseudoboletia maculata and Toxopneustes pileolus, which prefer to cover themselves with coral rubble and other calcified material. Only in Toxopneustes pileolus did we find a significant corresponding depth-dependent decrease in total cover area, confirming previous work that covering behavior serves as a protection mechanism against UV radiation. We found no dependence of particle size on either species or size of sea urchin, but we observed that larger sea urchins generally carried more and heavier debris. We observed a transport mechanism of debris onto the echinoid body surface utilizing a combination of tube feet and spines. We compare our results to previous studies, comment on the phylogeny of sea urchin covering behavior, and discuss the interpretation of this behavior as animal tool use.